ON THE NATURE OF OXIDE FERROMANGANESE ORES OCEAN - V. V. AVDONIN; E. A. ZHEGALLO; N. E. SERGEEVA (Известия высших учебных заведений: Геология и разведка, 2018)
Oxide ores of the global ocean — cobalt-rich crusts and ferromanganese nodules are of bacterial origin and identified as  stromatolites and onkolites. Pillar structure of ferromanganese  stromatolites and festoon-shaped structures of onkolites represent  the bacterial mats, formed by interbedding of fossilized bacterial  biofilms. The appearance of ore-forming types of procaryotic family  and their evolution are defined by major biosphere events. On the  case study of the ferromanganese  nodules of Magellanic mountains and cobalt-rich crusts of the province  of the Clarion-Clipperton, the main stages of the evolution of structural  forms of bacterial communities have been revealed. It has been shown that the change of phases happened due to the influence of  major tectonic, volcanic and other geological events.